Stock Price Prediction of PT. Kimia Farma, Tbk Using Bayesian Ridge Algorithm - Iqbal, Aldy Mercyano; Setiadi, Indra Tresna; Pratama, Aditya Dhian; Imelda, Imelda (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
Stocks are proof of ownership of capital/funds in the company, a paper that clearly states the nominal value, and company name and is followed by an explanation of the rights and obligations to each shareholder, enough shares to be sold. Many companies from various sectors market their shares, one of which is PT. Kimia Farma, Tbk. This study aims to determine the performance of the Bayesian Ridge Regression algorithm to predict the closing price of PT Kimia Farma, Tbk's stock price. The data for these stocks was collected through the website id.investing.com with a data period of 2015 - 2022. Based on the test results, the Bayesian Ridge Regression algorithm can be used to predict stock prices with a good value where the R2 value is 0.9968 and RMSE value of 49.199 when modelling, R2 value is 0.9972 and RSME value is 45.400 when testing with new/testing data.